Anticipating total war the German and American experiences, 1871-1914 - Boemeke, Manfred F.; Chickering, Roger 1942-; Förster, Stig (Publications of the German Historical Institute, 1999)
These essays explore the discourse on war in Germany and the United States between 1871 and 1914 - in the era bounded by the mid-century wars in Europe and North America and the First World War. The concept of 'total war', which was prefigured in aspects of the earlier conflicts and realized in 1914, provides the analytical focus. The essays reveal vigorous discussions of warfare in several forums - among soldiers, statesmen, women's groups and educators - on both sides of the Atlantic. Predictions of long, cataclysmic wars were not uncommon in these discussions, while the involvement of German and American soldiers in colonial warfare suggested that future combat would not spare civilians. Despite these 'anticipations of total war', virtually no one drew the practical implications in planning for war in the early twentieth century